So you want to be president? - St. George, Judith, 1931-; Small, David, 1945- (New York : Philomel Books, 2000)
Presents an assortment of facts about the qualifications and characteristics of U.S. presidents, from George Washington to Bill Clinton.
Includes bibliographical references.
Caldecott Medal/Honor.
School Library Journal starred.
Wilson's Children.
Booklist starred, July 2000.
Bulletin (Center for Children's books), July 2000.
Keywords: Presidents -- United States -- Miscellanea -- Juvenile literature; Presidents -- Miscellanea; Presidents -- United States -- Miscellanea